Quel rôle pour les scénarios Facteur 4 dans la construction de la décision publique ? - Sandrine Mathy; Meike Fink; Ruben Bibas (Développement Durable et Territoires)
Seven long-term prospective studies representing the energy trajectories consistent with a Factor Four, i.e. a 75% reduction of greenhouse gases emissions in 2050 in France have been identified. We analyze their methodology and the high dispersion of results. Then we discuss the role of scenario-making. Among them, only one of the scenarios achieves the Factor Four, thereby showing the limitations of these studies. On the methodological side, the engineering models used appear as black boxes, each using their own technological hypotheses and not readily understandable by the non-specialist. Therefore, exchanges between modelers, economists, technologists, sociologists and representatives of the civil society are a key factor for these scenario elaboration as their legitimacy stems from social and politic appropriation of scientific results.